2006
DOI: 10.1021/bi061802v
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Recognition by the Hetero-Octameric ATP Phosphoribosyltransferase from Lactococcus lactis

Abstract: Two families of ATP phosphoribosyl transferases (ATP-PRT) join ATP and 5-phosphoribosyl-1 pyrophosphate (PRPP) in the first reaction of histidine biosynthesis. These consist of a homohexameric form found in all three kingdoms, and a hetero-octameric form largely restricted to bacteria. Hetero-octameric ATP-PRTs consist of four HisG S catalytic subunits related to periplasmic binding proteins, and four HisZ regulatory subunits that resemble histidyl-tRNA synthetases. To clarify the relationship between the two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 42 publications
(88 reference statements)
0
45
0
Order By: Relevance
“…Previous work suggested that LlaHisG S is inactive without LlaHisZ [3]. By performing in vitro enzyme kinetics assays with a LlaHisG S concentration greater than previously reported [15], we detected phosphoribosyltransferase activity of LlaHisG S in vitro. ATP-PRT activity was also observed in vivo, as an E. coli hisG knockout strain transformed with a plasmid encoding LlaHisG S was able to proliferate in the absence of an exogenous histidine source.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Previous work suggested that LlaHisG S is inactive without LlaHisZ [3]. By performing in vitro enzyme kinetics assays with a LlaHisG S concentration greater than previously reported [15], we detected phosphoribosyltransferase activity of LlaHisG S in vitro. ATP-PRT activity was also observed in vivo, as an E. coli hisG knockout strain transformed with a plasmid encoding LlaHisG S was able to proliferate in the absence of an exogenous histidine source.…”
Section: Discussionmentioning
confidence: 48%
“…histidine [12,13,15]. Despite the structural similarity between a single chain of HisG S and HisG L , the short form and long form ATP-PRTs differ in their quaternary structure.…”
mentioning
confidence: 99%
“…PRPP-binding loops have been identified in ATP phosphoribosyltransferases of L. lactis (148-Gly-Leu-Ala-Asp-Ala-Ile-Val-Asp-IleVal-Glu-Thr-Gly-Asn-Thr-162) (281) and of the hyperthermophilic bacterium T. maritima (140-Gly-Leu-Ser-Asp-Leu-Ile-Val-Asp-Ile-Thr-Glu-Thr-Gly-Arg-Thr-155) (282). Mutations that replaced Thr159 or Thr162 of L. lactis ATP phosphoribosyltransferase confirmed the importance of this sequence in PRPP binding (283). (Fig.…”
Section: Reactions At the Anomeric Carbon Of Prppmentioning
confidence: 86%
“…PRTases are classified into four subclasses (types I, II, III, and IV) according to their structures [15], [22][26]. QAPRTase is a type II PRTase that participates in the de novo pathway of the pyridine coenzyme NAD [7], [15].…”
Section: Introductionmentioning
confidence: 99%